2017
DOI: 10.1111/1365-2664.12878
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil microbial communities due to biological invasions can reduce allelopathic effects

Abstract: Summary Soil microbes are important in mediating allelopathic interactions between invasive and native plants in the field. However, it was not known how these interactions vary in the process of biological invasions and the effects of soil microbes; this knowledge may facilitate understanding the dynamics and mechanisms of biological invasions and managing invaded ecosystems. We conducted competition and seed germination experiments to determine the allelopathic effects of Ageratina adenophora in soils from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Multiple studies have shown significant impacts of invasive plant populations on soil microbial communities (Xu et al, 2012;Li et al, 2017;Malinich et al, 2017); however, such an effect on airborne microbes has received no attention. In fact, plants contribute microbes to the air around them (Lymperopoulou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown significant impacts of invasive plant populations on soil microbial communities (Xu et al, 2012;Li et al, 2017;Malinich et al, 2017); however, such an effect on airborne microbes has received no attention. In fact, plants contribute microbes to the air around them (Lymperopoulou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that strong allelopathy (Inderjit et al, 2011) and high resource capture and use efficiency (Wang et al, 2013) promote its competitive advantages over native species. Recent studies have shown that A. adenophora frequently changes soil microbial communities to contribute to its invasion (Xu et al, 2012;Li et al, 2017;Zhu et al, 2017). In addition, Mei et al (2014) indicated that the diversity and isolation frequency of foliar fungal endophytes have increased with time since the introduction of A. adenophora.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have observed that soil microbes play an important role in determining allelopathic activity [28,74]. In the present study, the effects of allelopathy and soil microbes, the latter being explored by comparison of plant growth between sterilized and non-sterilized soil, showed opposing effects for P. americana growth (Figure 2).…”
Section: The Effects Of Soil Microbes On Plant Growthmentioning
confidence: 64%
“…We calculated the response index (RI) [28,58] to evaluate the allelopathic effects of forest litter on P. americana seed germination and seedling growth, as follows: (Variable leachate − Variable water )/Variable water , where Variable leachate was the individual value of replicates with leachate application and Variable water the average value of replicates with water addition. RI > 0 indicates a positive effect, RI < 0 indicates an inhibitory effect, and RI = 0 indicates no effect.…”
Section: Discussionmentioning
confidence: 99%
“…herba-alba between previous laboratory studies and our field experiment might be because of differences in the experimental conditions, including the soil microbial community, level of exposure to allelopathic compounds, the specific mixture or the relative concentrations of compounds acting jointly under natural conditions. For instance, it is known that in the field, associated soil microorganisms can metabolize chemical compounds and diminish their allelopathic effects [ 55 , 56 ]. This emphasizes that laboratory studies might overestimate the significance of allelopathy in nature, as discussed in previous studies [ 57 60 ].…”
Section: Discussionmentioning
confidence: 99%